2021
DOI: 10.1108/acmm-03-2021-2449
|View full text |Cite
|
Sign up to set email alerts
|

Aminobenzoic acid functionalized graphene oxide as environment-friendly corrosion inhibitors for Q235 steel in HCl solution: experimental and DFT studies

Abstract: Purpose The purpose of this study is to provide effective and environmental-friendly corrosion inhibitors derived from graphene oxide for Q235 steel. Design/methodology/approach Nontoxic and environment-friendly 4-aminobenzoic acid was used to functionalize graphene oxide via amidation and diazotization. The obtained amidation 4-aminobenzoic acid functionalized graphene oxide (PAGO) and diazotization 4-aminobenzoic acid functionalized graphene oxide (PDGO) were characterized by FTIR, Raman and TEM, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…From Figure , the IE values of the modified GO corrosion inhibitor including bis (2-aminoethyl) amine-modified GO (NAEP-GO), octanoate-functionalized GO (SO-GO), cyclodextrin-based-functionalized GO (CD-GO), dopamine-functionalized GO (PD-GO), L-proline nitrate-functionalized GO (IL-GO), diaminodecane-functionalized GO (DAD-GO), and diaminododecane-functionalized GO (DADD-GO) were lower than 90%. The 4-aminobenzonic acid-functionalized GO (PA-GO) and diazotization 4-aminobenzonic acid-functionalized GO (PD-GO) showed higher corrosion inhibition efficiencies with IE values up to 98% . However, a larger dosage with a PA-GO concentration close to 40 mg L –1 was required.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From Figure , the IE values of the modified GO corrosion inhibitor including bis (2-aminoethyl) amine-modified GO (NAEP-GO), octanoate-functionalized GO (SO-GO), cyclodextrin-based-functionalized GO (CD-GO), dopamine-functionalized GO (PD-GO), L-proline nitrate-functionalized GO (IL-GO), diaminodecane-functionalized GO (DAD-GO), and diaminododecane-functionalized GO (DADD-GO) were lower than 90%. The 4-aminobenzonic acid-functionalized GO (PA-GO) and diazotization 4-aminobenzonic acid-functionalized GO (PD-GO) showed higher corrosion inhibition efficiencies with IE values up to 98% . However, a larger dosage with a PA-GO concentration close to 40 mg L –1 was required.…”
Section: Resultsmentioning
confidence: 99%
“…29−35 For example, 4-aminobenzoic acidfunctionalized GO have been prepared, and the IE value for Q235 steel in the acidic medium (1.0 M) was close to 98%. 33 Saleh et al reported that the IE value of sodium caprylatemodified GO for protecting CS in HCl aqueous solution (15 wt %) was up to 80%. 35 Haruna et al reported β-cyclodextrinmodified graphene oxide (CD-GO) exhibited good corrosion resistance against CS corrosion in HCl solution (1.0 M) with IE close to 81.17%.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic potential polarization curves showed the maximum inhibition efficiency of 96.45 % and 95.15 % for PAGO and PDGO, respectively, verifying the results of the EIS. PAGO and PDGO significantly hindered corrosion by adsorption on the steel surface [106] …”
Section: Modified Graphene Oxide Corrosion Inhibitormentioning
confidence: 99%
“…PAGO and PDGO significantly hindered corrosion by adsorption on the steel surface. [106] There are few studies on using functionalized GO as a corrosion inhibitor in highly acidic (15 % HCl) solutions. In all the studies, toxic solvents such as DMF, toluene, and THF were used for GO functionalization.…”
Section: Environmentally Friendly Modified Go Corrosion Inhibitormentioning
confidence: 99%